Flann O'Brien, The Collected Letters of Flann O'Brien, ed. Maebh Long (Victoria, TX: Dalkey Archive Press, 2018), xxxviii+603 pp., ISBN: 9781628971835, paperback, 26.00. Issue 2 (2021) - Taaffe, Carol
No abstract available